THE INFLUENCE OF LEADERSHIP AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE THROUGH WORKING DISCIPLINES AS INTERVENING VARIABLES - Fachrudi, Fachrudi; Parwoto, Parwoto; Saluy, Ahmad Badawi (Dinasti International Journal of Management Science, 2021)
The purposei of this studyi was to determine and analyze the influencei of leadershipi and organizationali commitment on worki discipline as well as the influence of leadership, organizational commitmenti and work disciplinei on employeei performance. This study uses primary data obtained from distributing questionnaires containing respondents' opinions about employee performance from the perspective of leadership, organizational commitment, and work discipline in one of the routes handled by the company. The sampling method used was convenience sampling. Of the population of 50 taken, all of them become the sample of this study. The analytical method used is SEM PLS using SmartPLS 3.2 software. The results of this study indicate that leadership has no effect on work discipline and employee performance, nor does it have an indirect effect on employee performance through work discipline. Meanwhile, organizational commitment has a significant positive effect on work discipline and employee performance, and has an indirect effect on employee performance which is partially mediated by work discipline. Likewise, work discipline has a significant positive effect on employee performance.